Korkeimman oikeuden näyttöprejudikaatit ja vapaa todistusharkinta - Rasilainen, Aki (Lakimies, 2023)
The free evaluation of evidence and The Supreme Court’s precedents on evaluation of evidence In the past decade, the Supreme Court of Finland has set more than 20 precedents on the evaluation of evidence, especially in sexual crimes. The principle of free evaluation of evidence has been in force in Finland since 1948. The historical purpose of the principle in the 20th century was to secure the individual treatment of people involved in the trial. The then prevailing statutory theory of proof was not able to do that. In the article, it is claimed that the Supreme Court’s activity in the field of evaluation of evidence is jeopardizing that purpose. In the law, the examination of evidence is set free, so that the rules of experience could be applied instead of legal guidelines when evaluating the evidence. The precedent decisions of the Supreme Court have a strong de facto steering effect in Finland. The Supreme Court has ruled that the testimony of the injured party alone can only exceptionally be sufficient evidence. The main rule is that the testimony of the injured party alone is not enough, but exceptionally it can be enough if the testimony can be found to be error-free by objective evaluation with acceptable criteria. With these legal guidelines, all injured parties are formally placed in the same position in the evaluation of evidence, regardless of their personal characteristics and ability to tell their true experiences. The exceptionally talented narrator, on the other hand, is placed in a different position. The main rule about the insufficiency of the testimony of the injured party is problematic because the testimony alone has no probative value at all, regardless of it’s content. The exception rule, on the other hand, is problematic because it puts the injured parties in a different position based on their personal characteristics and ability to tell their true experiences. This is apt to form discriminatory structures created by law. In the legal guidelines, persons cannot be treated as individuals, but as members of a group established by the guideline, who are united by a similar legal status. In the author’s opinion, free evaluation of evidence means that it follows the rules of experience applicable on a case-by-case basis. This becomes impossible if legal guidelines must be followed, where people cannot be treated as individuals. The demand for individual treatment of a person is the most important legal right, which the principle of free evaluation of evidence has been intended to protect throughout history. It is the cornerstone of a rule of law that recognizes human rights, which should not be lightly undermined.